Nonmonotonic Inheritance in Object‐Oriented Deductive Database Languages - May, Wolfgang; Kandzia, Paul‐Thomas (Journal of logic and computation, 2001)
Deductive object‐oriented frameworks integrate logic rules and inheritance. There, specific problems arise: due to the combination of deduction and inheritance, (a) deduction can take place depending on inherited facts, thus raising indirect conflicts, and (b) also the class hierarchy and ‐membership is subject to deduction. From this point of view, we investigate the application of the extension semantics of Default Logic to deductive object‐oriented database languages. By restricting the problem to Horn programs and a special type of defaults tailored to the semantics of inheritance, a forward‐chaining construction of a Herbrand‐style representation of extensions is possible. This construction is compared with the semantics for F‐Logic (and implemented in the FLORID system) which is based on a combination of classical deductive fixpoints and an inheritance‐trigger mechanism. We show that the F‐Logic semantics coincides with the standard semantics of Default Logic and Inheritance Networks.